MATHEMATICS LEARNING THROUGH CHARACTER EDUCATION BASED ON INTEGRATED THEMATIC LEARNING: A DEVELOPMENT OF LEARNING MATERIALS - Yenny Suzana; Sabaruddin Sabaruddin; Suesthi Maharani; Zainal Abidin (Jurnal Infinity, 2021)
This research is to develop mathematics teaching materials that are integrated with elementary school thematic learning. The purpose of the development is to obtain mathematics teaching materials that prioritize the local wisdom of the Acehnese people. This teaching material is helpful for fifth-grade elementary school students in which there are character values for learning mathematics. This study uses a qualitative descriptive research method with the ADDIE model development research design. This research focuses on analyzing elementary school teachers who face the problem of integrated mathematics-based character education in thematic learning, then making initial designs and developing character education-based mathematics teaching materials that are integrated into the learning theme. The results showed that character education-based mathematics teaching materials were compatible with elementary students' thematic learning. Mathematics teaching materials focused on solving math problems for elementary students, integrating character values in mathematics with various themes in thematic learning by integrating each mathematics material into themes. The mathematics teaching materials developed were designed with various activities related to daily activities with straightforward language to be understood and made into a mathematical model.